A summary of environmental health studies in the city of Ostrava and the surrounding region in the Czech Republic - Tomášková, Hana; Tomášek, Ivan; Polaufová, Pavla; Šlachtová, Hana; Janoutová, Jana; Jiřík, Vítězslav; Janout, Vladimír (Central European Journal of Public Health, 2016)
AIM: This study is concerned with environmental health studies conducted in Ostrava (Czech Republic) and the surrounding region since the early nineties. METHODS: Various databases, journals and reports, including internal or unpublished reports, were reviewed to assess the individual publications. A brief description of the studies and main results were collated. RESULTS: The city of Ostrava and the surrounding region is an important industrial centre in the Czech Republic with a long-term heavy environmental and occupational disease burden. In spite of the theoretically assessed decline of health risks related to decreasing concentrations of compounds in the environment in recent years, it still poses a disproportionally high risk for the city residents. There are a number of studies suggesting supportive evidence, but they are highly variable in their approach to this topic resulting in a high uncertainty of observed associations and consistency of results. Most of the studies were focused on specific contexts, without any relation to environmental factors. CONCLUSIONS: A more systematic approach is needed to assess environmental health burden of diseases especially in relation to air pollution, based on the prospective cohort study, that would lead to sufficient new evidence for accurate and updated description of the environmental health burden in Ostrava.
Keywords: environmentální zdraví; látky znečišťující vzduch; Environmental Health; Particulate Matter; vystavení vlivu životního prostředí; lidé; Environmental Exposure; Czech Republic; Air Pollutants; Air Pollution; Humans; průmysl; Industry; pevné částice; znečištění ovzduší; Česká republika